The Genetic Basis of Delayed Puberty - Howard, Sasha R. (Frontiers in Endocrinology, 2019)
Delayed pubertal onset has many etiologies, but on average two-thirds of patients presenting with late puberty have self-limited (or constitutional) delayed puberty. Self-limited delayed puberty often has a strong familial basis. Segregation analyses from previous studies show complex models of inheritance, most commonly autosomal dominant, but also including autosomal recessive, bilineal, and X-linked. Sporadic cases are also observed. Despite this, the neuroendocrine mechanisms and genetic regulation remain unclear in the majority of patients with self-limited delayed puberty. Only rarely have mutations in genes known to cause aberrations of the hypothalamic-pituitary-gonadal axis been identified in cases of delayed puberty, and the majority of these are in relatives of patients with congenital hypogonadotropic hypogonadism (CHH), for example in the FGFR1 and GNRHR genes. Using next generation sequencing in a large family with isolated self-limited delayed puberty, a pathogenic mutation in the CHH gene HS6ST1 was found as the likely cause for this phenotype. Additionally, a study comparing the frequency of mutations in genes that cause GnRH deficiency between probands with CHH and probands with isolated self-limited delayed puberty identified that a significantly higher proportion of mutations with a greater degree of oligogenicity were seen in the CHH group. Mutations in the gene IGSF10 have been implicated in the pathogenesis of familial late puberty in a large Finnish cohort. IGSF10 disruption represents a fetal origin of delayed puberty, with dysregulation of GnRH neuronal migration during embryonic development presenting for the first time in adolescence as late puberty. Some patients with self-limited delayed puberty have distinct constitutional features of growth and puberty. Deleterious variants in FTO have been found in families with delayed puberty with extremely low BMI and maturational delay in growth in early childhood. Recent exciting evidence highlights the importance of epigenetic up-regulation of GnRH transcription by a network of miRNAs and transcription factors, including EAP1, during puberty. Whilst a fascinating heterogeneity of genetic defects have been shown to result in delayed and disordered puberty, and many are yet to be discovered, genetic testing may become a realistic diagnostic tool for the differentiation of conditions of delayed puberty.